Starch granules and their size distribution in wheat: Biosynthesis, physicochemical properties and their effect on flour-based food systems - Lei Guo; Heng Chen; Yizhi Zhang; Shuai Yan; Xueyan Chen; Xin Gao (2023)
Starch is a vital component of wheat grain and flour, characterized by two distinct granule types: A-type starch (AS) with granules larger than 10 μm in diameter, and B-type starch (BS) with granules measuring no more than 10 μm in diameter. This review comprehensively evaluates the isolation, purification, and biosynthesis processes of these types of granules. In addition, a comparative analysis of the structure and properties of AS and BS is presented, encompassing chemical composition, molecular, crystalline and morphological structures, gelatinization, pasting and digestive properties. The variation in size distribution of granules leads to differences in physicochemical properties of starch, influencing the formation of polymeric proteins, secondary and micro-structures of gluten, chemical and physical interactions between gluten and starch, and water absorption and water status in dough system. Thus, starch size distribution affects the quality of dough and final products. In this review, we summarize the up-to-date knowledge of AS and BS, and propose the possible strategies to enhance wheat yield and quality through coordinated breeding efforts. This review serves as a valuable reference for future advancements in wheat breeding.